2019
DOI: 10.1037/cns0000165
|View full text |Cite
|
Sign up to set email alerts
|

A survey exploring synesthetic experiences: Exceptional experiences, schizotypy, and psychological well-being.

Abstract: We used an online survey to investigate the relations among synesthesia, schizotypy, exceptional experiences (ExEs), and well-being. Participants (N ϭ 1,628 [listwise N ϭ 767]; male ϭ 619, female ϭ 1,064) completed a Synesthesia Experience Questionnaire (SEQ), a general question about synesthetic experiences (Hartmann, 1991), the Anomalous Experience Subscale (AES) of the Anomalous Experience Inventory (Gallagher, Kumar, & Pekala, 1994), questions about parapsychological experiences, a multidimensional measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 73 publications
(149 reference statements)
0
17
0
1
Order By: Relevance
“…The aim is then not to demonstrate the existence of psi but rather to describe its biological foundations. For example, phenomenological and neurobiological aspects of synesthesia can be evaluated ( Eagleman et al, 2007 ), and psi might have a lot in common with synesthesia ( Simmonds-Moore et al, 2019 ). So, if the profound nature of psi cannot be explained, reliable markers correlated with its expression using fMRI or EEG studies could be determined in order to find neuro-correlates of psi ( Moulton and Kosslyn, 2008 ).…”
mentioning
confidence: 99%
“…The aim is then not to demonstrate the existence of psi but rather to describe its biological foundations. For example, phenomenological and neurobiological aspects of synesthesia can be evaluated ( Eagleman et al, 2007 ), and psi might have a lot in common with synesthesia ( Simmonds-Moore et al, 2019 ). So, if the profound nature of psi cannot be explained, reliable markers correlated with its expression using fMRI or EEG studies could be determined in order to find neuro-correlates of psi ( Moulton and Kosslyn, 2008 ).…”
mentioning
confidence: 99%
“…Other studies describing the psychological and/or neuropsychiatric profiles of synaesthetes using tools designed to measure levels of disorder-related traits in healthy populations (e.g. the Autism-Spectrum Quotient or the Oxford-Liverpool Inventory of Feelings and Experiences, O-LIFE) have shown that synaesthetes are only subtly different from nonsynaesthetes on these other dimensions [19,20,44,50]. Informed by these results, we framed synaesthesia in this study as a binary trait that may have modest quantitative relationships with aspects of other neurological traits at the genetic level.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the MMSI-2 represents a useful instrument for assessing abnormal experiences because it includes the main psychological indicators that predict these experiences. For example, a person who has had a "psi" experience and obtains high levels of schizotypy (Ez) may have experienced an attenuated hallucination of a psychotic nature rather than a delusion (Simmonds-Moore et al, 2019). However, if this person scored low on schizotypy and the other subclinical variables, it is possible that he or she would have had a non-pathological delusion.…”
Section: Conceptual Analysis Derived From the Theoretical Backgroundmentioning
confidence: 99%